Physical femóle beauty in lite Greek myth: ¿reward or punishment? (Iter, 2022)
In the Greek myth. beauty is regarded as a pleasant gift to divine and human eyes. Weshould not forget that three goddesses. who are w ornen at last. disputed an apple with theinscription “tt) xocXXÍott| " and they broke out a war. We should also think about the numerousepithets given to gods and moríais with kalli- as first component.•Yoír. if we circumscribe our view to a human and Jema le sphere. the basic question of thisresearch is to solve whether a splendid body results in a reward or a punishment. Amongothers. attractive characteristics are grace. proportion. freshness. slender. harmony. elegance.all of them accompanied by refmement in gestare and manners. by prudence and melody ¡nthe word. good taste in hairdressing. the clothes and the accessories plus uncountable persuasiveresources related to the figure and the bearing. The female possessors can be aware of suchpower and take advantage of it or ignore their own charm and cause more troubles to otherpeople - and to themselves-,The re are different grades of perception of the authority they exert. some times involuntarilyand dijferent levels of vanity\ Such is the case of the boastful Cassiepeia. Andrómeda' smother. who knew she was pretty' indeed and openly competes against the Nereids. Slaves arenot an exception: the post Homeric tradition imagined that the captive Briséis was tall.brunette and of radiant eyesight.
Keywords: physical beauty' - woman - Greek myth - reward - punishment